P112 Association of Cryptococcosis and Tuberculosis in a Patient With Crohn's Disease - A Challenging Diagnosis. (December 2019) - Santo, Paula; Zaltman, Cyrla; Santos, Paula; Valente, Fabricio; Costa, Marcio; Silveira, Monique; Barroso, Paulo
Abstract : CASE: A 23-years-old man born in Rio de Janeiro with established ileocolonic Crohn's disease (CD), eight years after the onset of symptoms. He started combination therapy (azathioprine and infliximab) after negative TB screening (negative PPD, normal chest x-ray). After six months, he was in clinical remission and presented with fever and headache lasting for one week. BMI was 16 kg/cm 2 . Laboratory findings showed an elevated ESR (90 mm/hr) and CRP level (23 mg/L), but white blood cells count was normal. Both drugs were discontinued and the patient was admitted. Cranial computed tomography (CT) was unremarkable. CT of the chest showed pleural thickening, fibro-atelectatic bands, and bronchiectasis in the upper left lobe, with calcified nodules, suggesting TB sequelae. CT of the abdomen showed splenomegaly and multiple small hypodense nodules. Abdominal MRI revealed that the lesions were isointense in T1, slightly hyperintense in T2, with a restricted-diffusion pattern, compatible with splenic abscesses. Echocardiogram was normal. HIV, EBV, CMV, HSV serology and serum latex-cryptococcus antigen test were negative. Hemoculture and urine cultures were negative. Sputum bacilloscopy and culture were also negative. Bronchoscopy with bronchoalveolar lavage fluid (BALF) showed culture and direct microscopic examination positives for cryptococcal infection. Due to the findings of splenic lesions, there was strong evidence of cryptococcal dissemination, and a lumbar puncture was performed. CSF analysis was normal, latex-cryptococcus antigen test, microscopic examination and culture were negative, excluding CNS involvement. He was discharged home with fluconazole 400 mg PO QD and his symptoms gradually subsided after 2 weeks. Three months after releasing azathioprine, it was necessary to be reintroduced due to a CD flare. After one month, he presented cough and pleuritic chest pain. Chest CT showed ground-glass opacification, and his symptoms improved with antibiotic therapy. Abdominal CT demonstrated an increase in the number and size of the spleen abscesses. A diagnostic laparoscopy with peritoneal lavage and biopsy was scheduled to investigate the etiology of splenic abscesses. However, as pleuritic chest pain and cough returned before that, he went to the emergency room where a new chest CT showed typical signs of pulmonary TB. Sputum culture confirmed the diagnosis. Hence, the abdominal findings were attributed to disseminated TB. He was discharged home with rifampin, isoniazid, pyrazinamide, and ethambutol, and will be followed up until clinical and radiologic response. This case illustrates two concomitant opportunistic infections associated with CD treatment with a clinical and radiological worsening related to an Immune Reconstitution Inflammatory Syndrome after azathioprine and infliximab withdrawal. Clinical reasoning was essential for definitive diagnosis. The possibility of two concomitant life-threatening infections with atypical manifestations in IBD patients should always be evaluated, mainly in Latin America.